Patients with primary myelofibrosis: treatment and quality of life - L. M. Meshcheryakova; O. V. Porotkova; L. G. Kovaleva; L. Yu. Kolosova (Онкогематология, 2014)
Primary myelofibrosis (PMF) is one of the diseases that cannot be cured using modern methods of conservative therapy. Therefore, treatment aimed at reducing PMF severity and improving patient’s quality of life. In this article, a comparative analysis of treatment response and quality of life depending on therapy using was shown. Partial remission rate at approximately the same level after α-interferon treatment (55.3 %) and after cytotoxic drug (48.8 %) was observed. Significant improvement in quality of life during α-interferon treatment was revealed.